(untitled) - Walter Burkert (Cambridge, Massachusetts, 1985)
The book draws on archaeological discoveries, insights from other disciplines, and inscriptions in Linear B to reconstruct the practices and beliefs of the Minoan-mycenaean age. The major part of this book is devoted to the archaic and classical epochs. It describes the various rituals of sacrifice and libation and explains greek beliefs about purification. It investigates the inspiration behind the great temples - at Olympia, Delphi, Delos, and the Acropolis - discussing the priesthood, sanctuary, and oracles. Considerable attention is given to the individual gods, the position of the heroes, and belief about the afterlife. The different festivals are used to illuminate the place of religion in the society of the city-state. The mystery cults, at Eleusis and among the followers of Bacchus and Orpheus, are also set in this book. The book concludes with an assessment of the great classical philosophers' attitudes to religion
Keywords: greece; religion